Startup CXO : a field guide to scaling up your company's critical functions and teams - Blumberg, Matt; Birkeland, Peter M. (Wiley, 2021)
"This is an important topic to write about at this particular time because America's "startup revolution" continues to gather steam. There are only increasing numbers of venture capital investors, seed funds, and accelerators supporting increasing numbers of entrepreneurial ventures. While there are a number of books in the marketplace about CEOs and leadership, and some about individual functional disciplines (lots of books about the topic of Sales, the topic of Product Development), there are very few books that are practical how-to guides for any individual function, and none that wrap all these functions into a compendium that can be used by a whole startup executive team."--